2020
DOI: 10.1007/s00382-020-05138-0
|View full text |Cite|
|
Sign up to set email alerts
|

Weakened SST variability in the tropical Atlantic Ocean since 2000

Abstract: A prominent weakening in equatorial Atlantic sea surface temperature (SST) variability, occurring around the year 2000, is investigated by means of observations, reanalysis products and the linear recharge oscillator (ReOsc) model. Compared to the time period 1982-1999, during 2000-2017 the May-June-July SST variability in the eastern equatorial Atlantic has decreased by more than 30%. Coupled air-sea feedbacks, namely the positive Bjerknes feedback and the negative net heat flux damping are important drivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 67 publications
10
52
1
Order By: Relevance
“…Atlantic diminished during the recent decades, as reported by Prigent et al (2020). Lower zonal wind stress variability tends to reduce EKW activity that is an important driver of SST in the ABA.…”
Section: 1029/2020gl089348mentioning
confidence: 63%
See 1 more Smart Citation
“…Atlantic diminished during the recent decades, as reported by Prigent et al (2020). Lower zonal wind stress variability tends to reduce EKW activity that is an important driver of SST in the ABA.…”
Section: 1029/2020gl089348mentioning
confidence: 63%
“…This lack of surface warming denotes an 11% amplification of the mean SST annual cycle in that region. Recently, Prigent et al (2020), using observations and reanalysis products, found that the equatorial Atlantic interannual SST variability in May-June-July has reduced by 31% during 2000-2017 relative to 1982-1999. Interannual SST variability in the equatorial Atlantic and Angola-Benguela area (ABA) are strongly connected Lübbecke et al, 2010;Reason et al, 2006). Hence, it may well be that the SST variability in the southeastern tropical Atlantic also has undergone a reduction since 2000, which is the topic of this study.…”
Section: Introductionmentioning
confidence: 99%
“…The interannual climate variability over the equatorial Atlantic has weakened during the recent decades (Tokinaga & Xie, 2011; Prigent et al, 2020). However, it remains unclear how the warming hole is related to changes in interannual variability, including fluctuations in the SST variance and spatial structure (Martín‐Rey et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The only substantial difference between the results presented here and the previous results was that the eastern Atlantic was significantly more active (at the 99% confidence level) even when considering the small sample size. This may be due to increased SSTs over this part of the Atlantic during the last decade (e.g., [40]). A comparison of the length of the TC season (not shown here) to previous results [1] would demonstrate that the Atlantic Region TC season may be beginning about 2 weeks earlier than June 1 as TCs were observed in May for 5 of the 10 years during this decade.…”
Section: Interannual and Interdecadal Variabilitymentioning
confidence: 99%